Method for achieving high-strength and high-energy-absorption aluminum alloy laser additive manufacturing through active segregation
Through active segregation technology and high laser energy density input, the aluminum alloy material is induced to form a brittle precipitation phase distributed along the boundary of the melt pool in the laser powder bed melting LPBF technology, solving the shortcomings of the existing aluminum alloy structure in terms of buffering energy absorption effect, and achieving high-strength and high-energy absorption characteristics of aluminum alloy structure forming.
Patent Information
- Application Number
- CN202411938906.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
The aluminum alloy structure formed by the existing laser powder bed molten LPBF technology is limited in terms of buffering and energy absorption effect, and insufficient plastic deformation energy, resulting in poor energy absorption effect.
Through active segregation technology, artificially modified aluminum alloy matrix materials with precipitation strengthening and segregation characteristics are selected, combined with the anisotropic characteristics of laser stack fabrication and high laser energy density input, induced to form a brittle precipitation phase distributed along the boundary of the melt pool, enhance the difference between the yield strength and tensile strength of the material, and extend the plastic deformation interval.
The formation of the aluminum alloy structure with high strength and high energy absorption characteristics has been achieved, which significantly improves the difference between yield strength and tensile strength, extends the plastic deformation range, and enhances the buffering and energy absorption effect.
Smart Images

Figure CN119634749A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of energy-absorbing metal material manufacturing, and specifically relates to a method for realizing laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloys through active segregation. Background Art
[0002] Buffering and energy-absorbing components have important applications in the aerospace field. During the impact or collision, energy absorption occurs, and the energy is converted or converted into potential energy within the system. Energy-absorbing structures convert kinetic energy into potential energy through structural deformation. This energy transfer may be irreversible, such as plastic deformation energy, or reversible, such as elastic strain energy in the material. When designing foldable energy-absorbing structures, the main goal is to absorb a large part of the kinetic energy generated during the impact in an irreversible manner. This approach ensures minimal harm to personnel and equipment. These structures are usually made of materials that can deform or compress during impact, effectively absorbing energy and reducing the force transmitted to the spacecraft and its occupants. Existing buffering and energy-absorbing materials mainly include various metals and polymer materials processed into foam, honeycomb, and grid lattice shapes. With the improvement of service performance requirements, the elastomer itself also needs to have good buffering and energy absorption properties. When subjected to external impact, the elastomer can absorb energy during deformation to achieve a good buffering effect. Aluminum alloy structures are often used as the preferred material for buffering and energy-absorbing structures in the fields of aerospace, automobiles, etc. due to their low density and high specific strength. In order to enhance the irreversible energy absorption effect, it is necessary to increase its plastic deformation energy, that is, to increase the difference between yield strength and tensile strength, and to increase the plastic deformation range as much as possible to increase energy absorption.
[0003] Laser additive manufacturing technology can realize the integrated forming of complex components based on the layer-by-layer melting and deposition process. In particular, laser powder bed fusion (LPBF) technology based on the powder bed laying process can realize the layer-by-layer powder laying and laser selective melting and deposition process with micron-level layer thickness, which has important application prospects in the forming of precision and complex aluminum alloy lightweight energy-absorbing structures in the aerospace field. However, the current laser additive manufacturing forming of high-performance aluminum alloy materials often pursues high tensile strength, such as Al-Mg-Sc-Zr, ceramic particle reinforced aluminum matrix composites, etc. The difference between their yield strength and tensile strength is less than 50 MPa, resulting in a short plastic deformation range and poor buffering energy absorption effect. At present, LPBF forming of high-strength aluminum alloys with buffering energy absorption characteristics still faces two technical difficulties. First, the yield strength and tensile strength of aluminum alloys are often related to the intrinsic properties of the material. It is necessary to combine the material properties with the additive manufacturing forming process to design and develop a high-strength and high-performance aluminum alloy material system for buffering energy absorption applications. Second, laser additive manufacturing has the process characteristics of rapid melting and solidification, and layer-by-layer stacking. On the one hand, these process characteristics will cause the formed structure to deviate from the balanced solidification, bringing challenges to material design and manufacturing; on the other hand, they also make it possible to use this manufacturing characteristic to form new high-strength and high-energy absorption aluminum alloy structures.
[0004] In summary, LPBF technology has great advantages in the field of forming high-strength and high-energy absorption aluminum alloy structures for aerospace. However, there are problems such as limited plastic deformation energy and poor energy absorption effect of existing material systems. At present, there is no special material system and supporting process method to realize the integrated forming and manufacturing of high-strength and high-energy absorption aluminum alloy structures. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to address the problem of limited buffering and energy absorption effect of aluminum alloy structures formed by the existing laser powder bed fusion (LPBF) technology, and propose a method for laser additive manufacturing of aluminum alloys with high strength and high energy absorption characteristics through active segregation.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloys by active segregation, comprising the following steps: S1. Selection of materials prone to segregation: Select aluminum alloy matrix materials with precipitation strengthening, segregation characteristics and good laser powder bed melt formability; S2. Orientation of energy-absorbing structure: Based on the anisotropic characteristics of LPBF stacking formed by additive manufacturing, a buffer energy-absorbing structure is set along the vertical direction (Z direction); S3, additive forming preparation: drying the aluminum alloy matrix material powder, performing model layering and slicing and scanning path planning for the buffer energy absorption structure, and completing the additive manufacturing LPBF forming preparation; S4, process-induced segregation: Use a high laser energy density process parameter combination for laser additive manufacturing to induce the formation of brittle precipitation phases distributed along the molten pool boundary, and then perform aging post-treatment after forming to obtain the product.
[0007] Specifically, in step S1, the aluminum alloy matrix material is selected from any one of Al-Mn alloy, Al-Ni alloy, and Al-Fe alloy modified or not modified by trace elements.
[0008] Further, in step S1, when the unmodified Al-Mn alloy is selected, the content of the Mn element is 4.0-6.0 wt%; when the unmodified Al-Ni alloy is selected, the content of the Ni element is 4.0-6.0 wt%; when the unmodified Al-Fe alloy is selected, the content of the Fe element is 0.8-3.0 wt%.
[0009] Furthermore, in step S1, when Al-Mn alloy, Al-Ni alloy, Al-Fe alloy modified by trace elements is selected, the trace elements are selected from at least one of Sc, Zr, Ti, and Er, and the content of the trace elements in the modified alloy does not exceed 0.8wt.%.
[0010] Preferably, the aluminum alloy matrix material is powdered by atomization, the powder is spherical, and the particle size distribution range is 15-53 μm.
[0011] Furthermore, in step S2, according to the buffering energy absorption structure configuration, service scenario and the main load-bearing direction of the buffering, the buffering energy absorption direction of the component is consistent with the vertical Z direction of LPBF forming, that is, the vertical upward direction of printing is the buffering energy absorption direction.
[0012] Furthermore, in step S3, the aluminum alloy matrix material powder is dried in a vacuum atmosphere at 80-120° C. for 6 hours to improve the powder fluidity during the forming process.
[0013] Furthermore, in step S3, the thickness of the layered slices of the buffer energy absorption structure is between 30-50 μm; the substrate is calibrated before printing, and the oxygen content of the chamber atmosphere during the printing process is controlled within 50 ppm.
[0014] Further, in step S4, the high laser energy density is calculated by the formula η = P / V D To constrain the range of process parameters, the laser energy density is 130 J / mm 3 ≥ η≥50 J / mm 3 ; The laser power is defined as P , unit W, range is 350-400 W; laser scanning speed is defined as V , unit: mm / s, interval: 800 mm / s-1200 mm / s; scanning interval is defined as h , unit μm, interval is 80-120μm; scanning layer thickness is defined as d, The unit is μm, and the range is 30-50μm.
[0015] Furthermore, in step S4, the conditions for the aging post-treatment are: temperature 300-325° C., aging time 4-6 h, heat treatment atmosphere is argon atmosphere, and cooling method is furnace cooling. Beneficial Effects
[0016] (1) The present invention takes additive manufacturing LPBF forming of high-strength and high-energy-absorbing aluminum alloy structures as the object, and preferably designs an alloy system with precipitation and segregation characteristics in the raw materials, and combines the anisotropic characteristics of laser lamination manufacturing with high laser energy density input to induce the controllable distribution and precipitation of brittle phases such as Al6Mn and Al6Ni at the boundary of the molten pool. These precipitated phases will cause local stress concentration and premature yielding during the load-bearing process of the component. The in-situ nano-precipitated phases inside the grains in the subsequent load-bearing structure will increase the fracture strength, thereby achieving a significant increase in the difference between yield strength and fracture strength, a prolonged plastic deformation stage, and an enhanced plastic deformation energy absorption effect, that is, realizing the integrated additive manufacturing of complex aluminum alloy structures with high strength and high energy absorption characteristics.
[0017] (2) The aluminum alloy structure formed by the method of the present invention has brittle precipitation phases such as Al6Mn and Al6Ni that are continuously distributed along the boundary of the molten pool in the vertical Z direction. It can protect key components, passengers, etc. from severe elastic impact by premature yielding and deformation due to local stress concentration during the stress process. At the same time, the increased plastic deformation range can significantly enhance the buffering and energy absorption effect, thereby achieving an improvement in the performance of the aluminum alloy energy absorption structure. At the same time, this method combines the additive manufacturing LPBF technology to achieve integrated and precise forming of any complex structure, further providing a technical basis for the design and manufacture of lightweight buffering and energy-absorbing aluminum alloy structures for aerospace. This method simultaneously solves the problem of poor energy absorption efficiency of aluminum alloy structures currently formed by laser additive manufacturing, broadens the application of laser additive manufacturing of complex buffering and energy-absorbing aluminum alloys, and has strong operability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0019] Figure 1The process flow chart of the method of the present invention is shown in FIG.
[0020] Figure 2 Schematic diagram of the energy-absorbing structure orientation in laser additive manufacturing of aluminum alloy with high strength and high energy absorption properties through active segregation.
[0021] Figure 3 This is a schematic diagram of the microstructure formed by the active segregation method proposed in the present invention.
[0022] Figure 4 It is a SEM image of the molten pool cross section of Example 1 in the specific implementation manner.
[0023] Figure 5 It is a SEM image of the molten pool cross section of Example 2 in the specific implementation manner.
[0024] Figure 6 It is a comparison image of stress-strain curves of Examples 1 and 2 in a specific implementation manner.
[0025] Figure 7 This is a SEM image of the molten pool cross section of the formed specimen in Example 8 in the specific implementation manner.
[0026] Figure 8 This is a SEM image of the molten pool cross section of the formed specimen in Example 9 in the specific implementation manner. DETAILED DESCRIPTION
[0027] The present invention can be better understood with reference to the following examples. Example 1
[0028] Combination Figure 1 The present invention provides a method for laser additive manufacturing of aluminum alloy with high strength and high energy absorption characteristics by active segregation, comprising the following steps: Step 1: Prefer an alloy system with precipitation strengthening characteristics and good laser powder bed melt formability. The selected material system is Al-Mn-Si-Sc-Zr alloy, where the alloy components are Mn 5.0 wt.%, Si 0.2 wt.%, Sc 0.7 wt.%, Zr 0.5 wt.%, and the balance is Al. The original material is spherical alloy powder with a powder particle size of 15-53 μm and D 50 The powder is dry and has good flowability.
[0029] Step 2: Active segregation to achieve high strength and high energy absorption characteristics. The process of energy absorption structure orientation in laser additive manufacturing of aluminum alloy is as follows: Figure 2As shown in the figure, for the aluminum alloy components with complex structures to be formed, the direction of bearing and absorbing energy is firstly arranged to be consistent with the vertical Z direction of LPBF forming. Then, pre-processing software such as Materialslise Magics is used for layered slicing. The layer thickness is selected as 30 μm.
[0030] Step 3: After completing the part placement and layering in step 2, prepare for additive manufacturing. First, dry the Al-Mn-Si-Sc-Zr original powder in step 1 at 120°C in a vacuum atmosphere for 6 hours to improve the powder fluidity during the forming process. The powder thickness is set to 30 μm. Perform substrate calibration before printing, and control the chamber atmosphere at 40 ppm during the printing process.
[0031] The additive process described in step 4 induces segregation. During the forming process, the laser energy density of the solid material is set to η =125 J / mm 3 Specifically, the fixed layer thickness is 30 μm, the scanning pitch is 100 μm, the laser power in the solid material area is 375W, and the laser scanning speed is 1000 mm / s. For aging treatment, the temperature is 325℃, the aging time is 4 h, the heat treatment atmosphere is argon atmosphere, and the cooling method is furnace cooling.
[0032] Figure 3 It is a schematic diagram of the microstructure of the high-strength and high-energy-absorbing aluminum alloy material formed by the method of the present invention. Figure 4 is an SEM image of the cross-section molten pool of the component formed in Example 1. It can be seen that a precipitate-enriched area distributed along the boundary is formed in the bottom area of the molten pool. These precipitates have pointed tetragonal characteristics and are about 2 μm in size. These precipitates are Al6Mn intermetallic compounds, which are formed by the in-situ reaction of the solid solution element Mn in the raw material with the Al matrix. In this embodiment, the Mn element content is relatively high (~5wt.%), and the laser energy density input is relatively large, which can promote the heat accumulation effect of the molten pool and the formation of growth effect. Al6Mn precipitate phases distributed along the boundary of the molten pool are formed in the initial solidification stage at the boundary of the molten pool. As the solidification process proceeds, the cooling and solidification rate of the middle part of the molten pool accelerate, which inhibits the nucleation and precipitation of the Al6Mn phase. Therefore, the final formation is as follows Figure 4 The microstructural features of segregation along the molten pool boundary are shown in Figure 1. Aging treatment causes solid-state phase transformation in the matrix, and the supersaturated solid solution decomposes into dispersed nano-precipitated phases, which increases the fracture strength. In the subsequent load-bearing process, the Al6Mn phase segregated along the molten pool boundary will induce local stress concentration and premature yielding during the Z-direction load-bearing process, thereby increasing the plastic deformation range and buffer energy absorption resistance. Example 2
[0033] The present embodiment is different from the embodiment 1 in that the alloy system described in step 1 is an Al-Mn-Si-Sc-Zr alloy, wherein the alloy components are respectively Mn 2.0 wt.%, Si 0.2 wt.%, Sc 0.7 wt.%, Zr 0.5 wt.%, and the balance is Al. The rest is the same as the embodiment 1. Example 3
[0034] The present embodiment is different from the embodiment 1 in that the alloy system described in step 1 is an Al-Mn-Si-Sc-Zr alloy, wherein the alloy components are respectively Mn 8.0 wt.%, Si 0.2 wt.%, Sc 0.7 wt.%, Zr 0.5 wt.%, and the balance is Al. The rest is the same as the embodiment 1. Example 4
[0035] The difference between this embodiment and the first embodiment is that the energy absorption structure orientation process is not performed in step 2, and the component buffering energy absorption bearing direction is perpendicular to the LPBF forming Z direction. The rest is the same as the first embodiment. Example 5
[0036] The difference between this embodiment and embodiment 1 is that when the additive process induces segregation in step 4, the energy density of the solid material is reduced. Specifically, the laser power is 350 W, the laser scanning speed is 1500 mm / s, the layer thickness is 50 μm, and the scanning interval is 120 μm. η =38.8 J / mm 3 . The rest is the same as Example 1. Example 6
[0037] The difference between this embodiment and embodiment 1 is that when the additive process induces segregation in step 4, the energy density of the solid material increases. Specifically, the laser power is 450 W, the laser scanning speed is 800 mm / s, the layer thickness is 30 μm, and the scanning interval is 100 μm. η =187.5 J / mm 3 . The rest is the same as Example 1. Example 7
[0038] The difference between this embodiment and the first embodiment is that after the laser process-induced segregation in step 4, no aging treatment is performed. The rest is the same as the first embodiment. Example 8
[0039] The present embodiment is different from the embodiment 1 in that the alloy system described in step 1 is an Al-Ni-Ti alloy, wherein the alloy components are respectively Ni 5.0 wt.%, Ti 0.6 wt.%, and the balance is Al. The rest is the same as the embodiment 1. Example 9
[0040] The present embodiment is different from the embodiment 1 in that the alloy system described in step 1 is an Al-Fe-Zr alloy, wherein the alloy components are respectively Fe 2.0 wt.%, Zr 0.5 wt.%, and the balance is Al. The rest is the same as the embodiment 1.
[0041] The formed specimens were cut, ground and polished, and stress-strain tensile tests were performed on the formed specimens along the actual buffer bearing direction under standard room temperature. The test results of different embodiments are shown in Table 1.
[0042] Table 1 Support removal effect and inner cavity surface roughness processed by different embodiments
[0043] As can be seen from Table 1: Comparison of Example 1 with Example 2 and Example 3 shows that this method has a good effect on aluminum alloy systems with precipitation strengthening characteristics. Figure 4 As shown, the cross-sectional SEM image of the sample formed by this method shows that there are Al6Mn segregated particles distributed along the boundary of the molten pool at the bottom of the molten pool. In the summary of the mechanical properties test along the load-bearing and energy-absorbing direction, it has a low yield strength of ~326 MPa, a high fracture strength of ~448 MPa, and a strength difference of more than 120 MPa, and an elongation of 11.5%. The surface can achieve the characteristics of premature yield and delayed fracture at this time, and achieve good buffering energy absorption characteristics. When the Mn content is too low (~2wt.%), the cross-sectional SEM image of the formed specimen is as follows Figure 5 As shown in the figure, Al6Mn segregation particles distributed along the molten pool boundary cannot be formed at this time. At this time, the yield strength is higher at 407 MPa, and the tensile strength is reduced to 431 MPa, with a difference of only ~25 MPa, and the buffering energy absorption characteristics are poor. Figure 6 The figure shows a comparison of the stress-strain curves of the formed specimens of Example 1 and Example 2. It can be seen that the Mn content range constrained by the method of the present invention, combined with the subsequent process, can effectively induce controllable segregation at the molten pool boundary, resulting in premature yield in the stress-strain curve. When the Mn content is low, premature yield cannot be achieved in combination with the process. At this time, the difference between the yield strength and the tensile strength is small, and the energy absorption effect of the specimen is poor. When the Mn content is too high (8wt.%), the yield strength and tensile strength of the formed specimen are significantly reduced. This is because the segregation is severe, resulting in premature failure of the component. Comprehensive comparison, when the Mn content is always high, the high-strength and high-energy absorption aluminum alloy laser additive manufacturing LPBF forming can be effectively achieved.
[0044] Comparing Example 1 with Example 4, when the energy absorption structure orientation process is missing, that is, the energy absorption bearing direction is inconsistent with the LPBF forming Z direction, the tensile strength and elongation of the formed specimen are relatively high, 487 MPa and 513 MPa, respectively. This is because during the horizontal bearing process, the continuous linear distribution of the segregation phase is parallel to the bearing direction, which will not cause premature failure. However, the difference between the yield strength and the tensile strength is about ~30 MPa, which cannot provide effective buffer bearing effect.
[0045] Comparing Example 1 with Examples 5 and 6, when the laser energy density is too low during the laser forming process, the heat accumulation of the molten pool during the forming process of the formed specimen is insufficient, and the segregation of Al6Mn cannot be effectively induced. At this time, the difference between the yield strength and the tensile strength is only ~30 MPa, and the buffering energy absorption effect is limited. When the laser energy density is too high, both the yield strength and the tensile strength are significantly reduced. This is because excessive heat accumulation leads to excessive segregation phases and rapid failure during the load-bearing process, and the formed specimen cannot meet the high strength requirements at this time.
[0046] Comparing Example 1 with Example 7, when there is no post-treatment aging process, the difference between the yield strength and tensile strength of the formed specimen is about ~70 MPa, and its buffering energy absorption characteristics are not as good as Example 1. This is because the aging heat treatment will coarsen the Al6Mn segregation at the molten pool boundary to a certain extent and promote the precipitation of nano-dispersed precipitation phases inside the grains. This will reduce the yield strength and increase the tensile strength, thereby significantly improving the comprehensive buffering energy absorption effect.
[0047] Figure 7 This is a SEM image of the cross section of the melt pool of the formed specimen of Example 8 in the specific implementation method. It can be seen that a continuous white precipitate phase is formed along the bottom of the melt pool of the Al-Ni specimen formed by the technical method of the present invention, that is, the premature yield phenomenon caused by segregation can be induced in the subsequent load-bearing energy absorption process to improve the energy absorption efficiency. The mechanical properties test results in Table 1 show that at this time, the yield strength of the formed specimen of Example 8 is 307 MPa, and the tensile strength is 405 MPa. The difference between the yield strength and the tensile strength is about 100 MPa Figure 8 This is a SEM image of the cross-section of the melt pool of the formed specimen of Example 9 in the specific implementation method. It can be seen that the controlled segregation of the melt pool boundary can also be achieved for the Al-Fe specimen. At this time, the stress-strain performance test in Table 1 shows that the difference between the yield strength and the tensile strength of the formed specimen is about 110 MPa, and the formed specimen has good energy absorption effect. Comparing Example 1 with Examples 8 and 9, the process method proposed in the present invention is universal for Al-Mn, Al-Ni, Al-Fe and other alloy systems, and can be used for a variety of aluminum alloy systems for additive manufacturing to achieve integrated manufacturing of aluminum alloy components with energy absorption characteristics.
[0048] The present invention provides a method and idea for realizing laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloys through active segregation. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.
Claims
1. A method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloys by active segregation, characterized in that: The steps include: S1. Selection of materials prone to segregation: Select aluminum alloy matrix materials with precipitation strengthening, segregation characteristics and good laser powder bed melt formability; S2. Orientation of energy-absorbing structure: Combined with the anisotropic characteristics of LPBF stacking formed by additive manufacturing, a buffer energy-absorbing structure is set along the vertical direction; S3, additive forming preparation: drying the aluminum alloy matrix material powder, performing model layering and slicing and scanning path planning for the buffer energy absorption structure, and completing the additive manufacturing LPBF forming preparation; S4, process-induced segregation: Use a high laser energy density process parameter combination for laser additive manufacturing to induce the formation of brittle precipitation phases distributed along the molten pool boundary, and then perform aging post-treatment after forming to obtain the product.
2. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 1 is characterized in that: In step S1, the aluminum alloy matrix material is selected from any one of Al-Mn alloy, Al-Ni alloy, and Al-Fe alloy modified or not modified by trace elements.
3. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 2, characterized in that: In step S1, when the unmodified Al-Mn alloy is selected, the content of the Mn element is 4.0-6.0 wt%; when the unmodified Al-Ni alloy is selected, the content of the Ni element is 4.0-6.0 wt%; when the unmodified Al-Fe alloy is selected, the content of the Fe element is 0.8-3.0 wt%.
4. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 2, characterized in that: In step S1, when Al-Mn alloy, Al-Ni alloy, Al-Fe alloy modified by trace elements is selected, the trace elements are selected from at least one of Sc, Zr, Ti, Er, and the content of the trace elements in the modified alloy does not exceed 0.8wt.%.
5. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 2, characterized in that: The aluminum alloy matrix material is powdered by atomization, the powder is spherical, and the particle size distribution range is 15-53 μm.
6. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 2, characterized in that: In step S2, according to the buffer energy absorption structure configuration, service scenario and main load bearing direction of the buffer, the buffer energy absorption direction of the component is aligned with the vertical Z direction of LPBF forming.
7. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 2, characterized in that: In step S3, the aluminum alloy matrix material powder is dried in a vacuum atmosphere at 80-120° C. for 4-6 hours.
8. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 2, characterized in that: In step S3, the thickness of the layered slices of the buffer energy absorption structure is between 30-50 μm; the substrate is calibrated before printing, and the oxygen content of the chamber atmosphere is controlled within 50 ppm during the printing process.
9. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 2, characterized in that: In step S4, the high laser energy density is calculated by the formula η = P / V D To constrain the range of process parameters, the laser energy density is 130 J / mm 3 ≥ η ≥50 J / mm 3 ; The laser power is defined as P , unit W, range is 350-400 W; laser scanning speed is defined as V , unit: mm / s, interval: 800 mm / s-1200 mm / s; scanning interval is defined as h , unit μm, interval is 80-120μm; scanning layer thickness is defined as d, The unit is μm, and the range is 30-50μm.
10. The method for laser additive manufacturing of high-strength and high-energy-absorbing aluminum alloy by active segregation according to claim 2, characterized in that: In step S4, the conditions for the aging post-treatment are: temperature 300-325° C., aging time 4-6 h, heat treatment atmosphere is argon atmosphere, and cooling method is furnace cooling.